Stearic acids at sn-1, 3 positions of TAG are more efficient at limiting fat deposition than palmitic and oleic acids in C57BL/6 mice - Chuah, Cheng Hock; Gouk, S.W.; Cheng, S.F.; Ong, A.S. (Cambridge University Press, 2014)
In the present study, we investigated the effect of long-acyl chain SFA, namely palmitic acid (16:0) and stearic acid (18:0), at sn-1, 3 positions of TAG on obesity. Throughout the 15 weeks of the experimental period, C57BL/6 mice were fed diets fortified with cocoa butter, sal stearin (SAL), palm mid fraction (PMF) and high-oleic sunflower oil (HOS). The sn-1, 3 positions were varied by 16:0, 18:0 and 18:1, whilst the sn-2 position was preserved with 18:1. The HOS-enriched diet was found to lead to the highest fat deposition. This was in accordance with our previous postulation. Upon normalisation of total fat deposited with food intake to obtain the fat:feed ratio, interestingly, mice fed the SAL-enriched diet exhibited significantly lower visceral fat/feed and total fat/feed compared with those fed the PMF-enriched diet, despite their similarity in SFA-unsaturated fatty acid-SFA profile. That long-chain SFA at sn-1, 3 positions concomitantly with an unsaturated FA at the sn-2 position exert an obesity-reducing effect was further validated. The present study is the first of its kind to demonstrate that SFA of different chain lengths at sn-1, 3 positions exert profound effects on fat accretion.